The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1017/s0003356100041313
|View full text |Cite
|
Sign up to set email alerts
|

Partition of fat, body composition and body condition score in mature cows

Abstract: Body condition score, assessed subjectively on the live animal, was related to the directly determined body composition of 73 mature, non-pregnant, non-lactating cows of Hereford x Friesian, Blue-Grey, Galloway, Luing and British Friesian genotypes. Relationships between condition score and chemically determined body fat were all very highly significant, and considered to be of value for predictive purposes. Differences between genotypes in the proportion of fat stored in the main depots of the body resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0
6

Year Published

1992
1992
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 12 publications
(13 reference statements)
5
73
0
6
Order By: Relevance
“…1995). Wright & Russel (1984) reported a strong relationship (r = 0.93) between the British condition scoring method and the proportion of physically dissected fat in 15 Friesian cows. The Australian method has been found to be closely related to chemically estimated body fat % in 10 mixed breed dairy cows (r = 0.86) (Hodge et al unpubl.…”
Section: Introductionmentioning
confidence: 97%
“…1995). Wright & Russel (1984) reported a strong relationship (r = 0.93) between the British condition scoring method and the proportion of physically dissected fat in 15 Friesian cows. The Australian method has been found to be closely related to chemically estimated body fat % in 10 mixed breed dairy cows (r = 0.86) (Hodge et al unpubl.…”
Section: Introductionmentioning
confidence: 97%
“…More specifically, BCS is an estimate of fat stores on the body (Ferguson et al, 1994) assessing subcutaneous fat cover over specific body regions (Wright and Russel, 1984). Wright and Russel (1984) found that BCS is a poor predictor of inter-and intramuscular fat, which together account for 35 to 45% of body fat (Roche et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Good body condition in cattle reflects high amounts of energy stores in body tissue (Wright & Rüssel, 1984). Changes in body condition, direction of body weight change and intake of dietary energy influence the duration of anoestrus after parturition (Wiltbank et al, 1962;Dunn & Kaltenbach, 1980) and during the prepubertal period in bovine females.…”
Section: Introductionmentioning
confidence: 99%